Legality of the application of direct means of compulsion in the context of constitutional guarantees – a legal procedural study - Kubanek, Anita (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
State bodies have a right to resort to state compulsion, i.e. to a group of compulsion means which are an attribute of the state only. One of the most severe forms of state compulsion is direct compulsion which is applied predominantly by public officials in order to protect the rights and liberty of an individual and to ensure public safety. These means are designed to force a person to subordination to the commands based on law, which may entail the use of physical force. The purpose of this paper is to present the procedure and rules of using direct compulsion means and to discuss the level of legal interference in the individual’s rights and liberty.